1st Malaysia International Counselling Conference 2014 (MICC 2014): "Best Practices for Best Practitioners in Counselling Services" - Nor Hasniah, Ibrahim (Faculty of Cognitive Science and Human Development, 2014)
1st Malaysia International Counselling Conference 2014 (MICC 2014): "Best Practices for Best Practitioners in Counselling Services", held from 29 October-31 October 2014 in Hilton Kuching,Sarawak,Malaysia. The conference is organized by the International Counselling Association of Malaysia (PERKAMA ) in collaboration with Universiti Malaysia Sarawak (UNIMAS), the Public Service Department of Malaysia(JPA) and the Public Service Psychology Officers Association of Malaysia (PSIPA). It is an educational programme that focuses on the field of Counselling with the aims to bring awareness about the current trend and development in counselling practices. The MICC2014 brings together experts from academic and industry to exchange ideas and experiences from knowledge to tackle real world issues such as vulnerability among underprivileged children, suicidal prevalence and domestic violence to skills to apply new counselling models such as aneurofeedback, resilient therapy and drug counselling.The conference also presents an excellent opportunity for participants to develop and to strengthen professional relationship and friendships. About 93 papers with 18 sub themes were submitted to the conference from seven countries. The sub themes are : Applied Cognitive Sciences in Counselling Practices, Applied Human Resources in Counselling Practices,Applied Psychology in Counselling Practices,Applied Social Sciences in Counselling Practices,Career Development and Counselling, Counselling Ethics, Counsellor Education and Supervision, Family, Adolescents and Children Counselling, Health and Wellness in Counselling,Multicultural counselling, Organizationalcounselling,Mental Health Counselling, Rehabilitation counselling, School Counselling, Spiritual counselling, Substance Abuse/Drug Counselling, Technology in Counselling,and Test and Assessment in Counselling.